Crystalline polyaryletherketone surface grafted carbon nanotube and preparation method thereof

Through the sulfonation reaction and the diazo salt reaction, the amino blocking agent containing sulfone group is grafted onto the surface of the carbon nanotube, solving the problem of insufficient interaction between the carbon nanotube and the crystalline polyaryletherketone, achieving efficient and high-temperature-resistant interface modification, and enhancing the performance of the material.

CN119591938AActive Publication Date: 2025-03-11JILIN UNIVERSITY
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411679555.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-11
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The lack of effective interaction between carbon nanotubes and crystalline polyaryletherketones leads to a weak interface and the prior art is difficult to achieve stable and high-temperature resistant chemical bond grafting, affecting the dispersion and performance of carbon nanotubes.

Method used

The amino blocking agent containing sulfone groups was prepared by sulfonation reaction, and the diazo salt reaction was used to electrochemically reduce and graft the surface of the carbon nanotube to form a high-temperature and corrosion-resistant phenyl group and the sulfone group, thereby achieving chemical bond grafting of crystalline polyaryletherketone.

Benefits of technology

The dispersion of carbon nanotubes and the interface interaction with polyaryletherketone are improved, the material's high temperature and corrosion resistance are enhanced, the preparation process is simplified and the reaction cycle is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591938A_ABST
    Figure CN119591938A_ABST
Patent Text Reader

Abstract

The invention discloses a crystalline polyaryletherketone surface grafted carbon nanotube and a preparation method thereof, and belongs to the technical field of carbon materials.The preparation method comprises the following steps that an amino end-capping reagent containing sulfuryl, a difluoro monomer, a bisphenol monomer and potassium carbonate are placed in sulfolane to be subjected to a polymerization reaction, and amino-terminated polyarylether is obtained; carrying out diazonium salt reaction on the amino-terminated polyarylether and nitrite tetrafluoroborate to obtain diazonium salt-terminated polyarylether; connecting the carbon nanotube with a cathode, immersing the carbon nanotube in an electrolyte containing diazonium salt-terminated polyarylether, and applying a reduction potential for reaction to obtain a polyarylether-grafted carbon nanotube; and carrying out hydrolysis reaction on the polyarylether grafted carbon nanotube in an acid environment to obtain the crystalline polyaryletherketone surface grafted carbon nanotube. According to the crystalline polyaryletherketone prepared by the invention, the surface of the crystalline polyaryletherketone is grafted and modified with the carbon nano tube, and the carbon nano tube is directly connected with a polymer through high-temperature-resistant and corrosion-resistant phenyl and sulfuryl, so that the crystalline polyaryletherketone has better high-temperature resistance and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbon materials, in particular to a crystalline polyaryletherketone surface-grafted carbon nanotube and a preparation method thereof. Background Art

[0002] Carbon nanotubes are one-dimensional carbon materials with the characteristics of large aspect ratio, large surface area and good conductivity. They are a kind of functional nano-reinforcement. However, due to the large aspect ratio and high surface energy of carbon nanotubes, they are easy to agglomerate and difficult to disperse. In addition, there is a lack of effective interaction between carbon nanotubes and crystalline polyaryletherketones, so the interface is relatively weak, which brings potential hidden dangers. Therefore, it is necessary to improve the dispersibility of carbon nanotubes and the interfacial interaction with polyaryletherketones by chemical bond grafting. There are four problems in grafting crystalline polyaryletherketones onto the surface of carbon nanotubes by chemical bonds: (1) In order to ensure that the resin matrix at the interface has good compatibility and the interface phase also has the same corrosion resistance and high temperature resistance as the polyaryletherketone resin matrix, it is necessary to graft the crystalline polyaryletherketone onto the surface of the carbon nanotubes; (2) The excellent corrosion resistance of crystalline polyaryletherketone results in the lack of effective solvents, making it difficult for effective chemical reactions to occur in the solid phase; (3) Functional groups such as ester groups, amide groups, aliphatic ether groups and alkyl groups are usually not resistant to high temperatures, and their decomposition temperatures are usually less than or equal to 300°C, which cannot meet the molding requirements of crystalline polyaryletherketone at 400°C. Therefore, grafting needs to be achieved through stable and high-temperature resistant chemical bonds; (4) Chemical bond grafting needs to be achieved efficiently.

[0003] A large number of carbon nanotube surface modification works based on chemical bond grafting have been carried out at home and abroad, but none of them can solve the above problems at the same time: CN114507356A discloses a method for grafting phenolphthalein type polyaryletherketone onto the surface of carbon nanotubes through ester groups, using a reducing agent to reduce the carbonyl group in the soluble phenolphthalein type polyaryletherketone (non-crystalline) in the solution state to a hydroxyl group, and then form an ester group with the carboxyl group on the surface of the carbon nanotube through an esterification reaction. This method not only fails to achieve chemical bond grafting of crystalline polyaryletherketone, but the ester group also does not have high temperature resistance. CN105838086B adopts a similar strategy to carry out a "solid-solid" phase sulfonation reaction between surface hydroxylated polyetheretherketone (insoluble) and surface sulfonated carbon nanotubes under suspension conditions. It not only faces the problem of poor heat resistance of the sulfonate structure, but also cannot overcome the problem of low "solid-solid" phase reaction efficiency. CN112940450B discloses a method for achieving grafting through click chemistry reaction between azide functional groups and carbon nanotube surfaces. It is based on methylated polyaryletherketone (insoluble and has poor heat resistance) and uses sodium azide to convert methyl groups into azide functional groups and then react with carbon nanotubes to achieve grafting. This method not only fails to achieve chemical bond grafting of crystalline polyaryletherketone, but also uses highly toxic and explosive sodium azide, which makes industrialization difficult. CN116874885A discloses a method for grafting soluble biphenyl terephthalate-resistant polyarylether by diazotization of carbon nanotubes. This method not only has a long grafting reaction time (5-30h), but also fails to achieve chemical bond grafting of crystalline polyaryletherketone.

[0004] CN109851731B discloses a method for functionalizing the surface of carbon nanotubes and achieving chemical bond grafting with polyetheretherketone by in-situ polymerization. The grafting process of this method is accompanied by the polymerization reaction of polyetheretherketone, and what is actually obtained is a carbon nanotube-doped polyetheretherketone composite material, but it is impossible to obtain a dispersible modified carbon nanotube. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing carbon nanotubes grafted on the surface of crystalline poly(aryletherketone) to solve the problems raised in the above background technology.

[0006] To achieve the above objectives, the embodiments of the present invention provide the following technical solutions: A method for preparing carbon nanotubes grafted onto the surface of crystalline poly(aryletherketone), comprising the following steps: The amide-containing sulfonyl halide compound and halogenated benzene are sequentially subjected to sulfonation reaction and acid hydrolysis reaction to obtain an amino-terminated agent containing a sulfone group; The amino-terminated agent containing a sulfone group, a difluoro monomer, a bisphenol monomer and potassium carbonate are placed in sulfolane to carry out a polymerization reaction to obtain an amino-terminated polyarylether; The amino-terminated polyarylether is subjected to a diazonium salt reaction with nitrite tetrafluoroborate to obtain a diazonium salt-terminated polyarylether; The diazonium salt-capped polyarylether is prepared into an electrolyte, the carbon nanotube is connected to a cathode, immersed in the electrolyte containing the diazonium salt-capped polyarylether, and a reduction potential is applied to react to obtain a carbon nanotube grafted with the polyarylether; The carbon nanotubes grafted with polyarylether are subjected to hydrolysis reaction in an acidic environment to obtain crystalline carbon nanotubes grafted with polyaryletherketone.

[0007] Preferably, the halogenated benzene is chlorobenzene or fluorobenzene.

[0008] Preferably, the step of sequentially subjecting the amide-containing sulfonyl halide compound and the halogenated benzene to a sulfonation reaction and an acidolysis reaction to obtain an amino-capping agent containing a sulfone group specifically comprises: Under the condition of no more than -5 ℃ and inert gas protection, the amide-containing sulfonyl halide compound is fully dissolved in the halogenated benzene, and AlCl3 powder is added in batches; then the temperature is raised to room temperature and stirred; the temperature is continued to be raised to reflux; deionized water is added to azeotropic reflux to separate the unreacted halogenated benzene; filtering and washing the filter residue to obtain a crude product; using ethanol to recrystallize the crude product three times, and drying to obtain a capping agent precursor; The capping agent precursor is dissolved in a mixture of concentrated hydrochloric acid and ethanol and refluxed; then extracted with ethyl acetate, the organic phases are combined and dried over anhydrous sodium sulfate; then filtered and concentrated to obtain an amino capping agent containing a sulfone group.

[0009] Preferably, the difluoro monomer is 4,4'-difluorobenzophenone imine and / or difluorodiketone imine; and the bisphenol monomer is at least one of hydroquinone, biphenol, 4,4'-dihydroxybenzophenone and 4,4'-dihydroxydiphenyl ether.

[0010] Preferably, the step of placing an amino-terminated agent containing a sulfone group, a difluoro monomer, a bisphenol monomer and potassium carbonate in sulfolane for polymerization to obtain an amino-terminated polyarylether specifically comprises: An amino end-capping agent containing a sulfone group, a difluoro monomer, a bisphenol monomer and potassium carbonate are added to cyclopentane sulfone at the same time; then toluene is added, the temperature is raised to azeotropic, and after toluene is refluxed for a certain period of time, the toluene is exhausted; the temperature is continued to be raised to not less than 210°C for reaction; then the material is discharged into ethanol, crushed, washed, and dried to obtain an amino-terminated polyarylether.

[0011] Preferably, the step of reacting the amino-terminated polyarylether with nitrosotetrafluoroborate to form a diazonium salt to obtain the diazonium salt-terminated polyarylether comprises: The amino-terminated polyarylether is dissolved in 1,4-dioxane; the above solution is added dropwise into an acetonitrile solution containing nitrite tetrafluoroborate; when the solution becomes a dark brown transparent solution, the material is discharged into ether, and the diazonium-terminated polyarylether is rapidly precipitated, which is filtered and washed with ether to obtain the diazonium-terminated polyarylether.

[0012] Preferably, the steps of preparing an electrolyte containing diazonium salt-capped polyarylether, connecting carbon nanotubes to a cathode, immersing the carbon nanotubes in the electrolyte containing diazonium salt-capped polyarylether, applying a reducing potential for reaction, and obtaining carbon nanotubes grafted with polyarylether specifically include: The diazonium salt-terminated polyarylether and supporting electrolyte are dissolved in acetonitrile to prepare an electrolyte solution; The carbon nanotubes are connected to a cathode, immersed in an electrolyte, and a reduction potential is applied to react. The electrochemically reduced carbon nanotubes are washed with acetonitrile and dried to obtain carbon nanotubes grafted with polyarylether.

[0013] Preferably, the supporting electrolyte is tetrabutylammonium tetrafluoroborate.

[0014] Preferably, the step of hydrolyzing the carbon nanotubes grafted with polyarylether in an acidic environment to obtain the crystalline polyaryletherketone surface-grafted carbon nanotubes specifically comprises: The carbon nanotubes grafted with polyarylether are placed in acetone, mechanically stirred and ultrasonically dispersed; then, hydrochloric acid is added dropwise under the conditions of mechanical stirring and ultrasonic dispersion, and the temperature is raised to reflux; then, filtration and washing are performed, and drying is performed to obtain crystalline polyaryletherketone surface grafted carbon nanotubes.

[0015] Another object of the present invention is to provide a crystalline polyaryletherketone surface-grafted carbon nanotube prepared by the above preparation method.

[0016] The present invention provides a method for preparing crystalline polyaryletherketone surface-grafted carbon nanotubes, wherein an amino-terminated agent containing a sulfone group is prepared, and the amino-terminated agent containing a sulfone group is used to realize a "one-pot method" for preparing amino-terminated polyarylether and diazonium-terminated polyarylether; the surface of the carbon nanotube is modified by using the diazonium-terminated polyarylether, the carbon nanotube can be directly connected to the polymer via the high-temperature and corrosion-resistant phenyl and sulfone groups, and the polyaryletherketone grafted on the surface of the carbon nanotube has crystallinity.

[0017] The raw materials used in the present invention are relatively cheap. The prepared amino end-capping agent containing a sulfone group can avoid the end-capping polymerization of "polymerization first and then end-capping" due to its high reactivity, realize the "one-pot" end-capping polymerization, and reduce the reaction cycle (omitting 2-6 hours of the post-end-capping process).

[0018] The crystalline polyaryletherketone surface grafted modified carbon nanotubes prepared by the present invention has better high temperature resistance and corrosion resistance because the carbon nanotubes are directly connected to the polymer through the high temperature and corrosion resistant phenyl and sulfone groups, avoiding the ester groups and other functional groups that are not resistant to high temperature and corrosion used in the traditional mechanism. In addition, since the crystalline polyaryletherketone is grafted to the surface of the carbon nanotubes through chemical bonds, it has better corrosion resistance.

[0019] The preparation method provided by the present invention avoids traditional esterification, amidation and other reactions, and uses electrochemical reduction as a grafting method. Due to the high reaction efficiency (3-5 min), it can achieve batch preparation of crystalline polyaryletherketone surface grafted modified carbon nanotubes. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is the structural formula of the carbon nanotube grafted with polyarylether prepared in the embodiment of the present invention; Figure 2 is the structural formula of the carbon nanotubes grafted on the surface of the crystalline polyaryletherketone prepared in the embodiment of the present invention; Figure 3 This is a Raman spectrum characterization result diagram of carbon nanotubes grafted on the surface of crystalline poly(aryletherketone) prepared in an embodiment of the present invention; Figure 4 The cyclic voltammetry curve of the electrochemical reduction grafting reaction provided by the embodiment of the present invention. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0022] The embodiment of the present invention firstly prepares an amino-terminated agent containing a diphenyl sulfone structure by a sulfonation reaction using a low-cost reagent, and utilizes its high reactivity (the higher the electron-withdrawing ability of the para-functional group of fluorobenzene, the higher the substitution reaction activity, which is reflected in the significantly lower polymerization reaction activity of 4,4'-difluorobenzophenone than that of 4,4'-difluorodiphenyl methyl sulfone) to achieve the preparation of an amino-terminated polymer; on this basis, a diazonium salt functional group is directly constructed at the polymer end group, and the purpose of grafting the polymer on the surface of carbon nanotubes is efficiently achieved by an electrochemical reduction reaction (3-5min). Finally, the polymer grafted on the surface of the carbon fiber is converted into a crystalline polyaryletherketone by a hydrolysis reaction. The present invention achieves surface grafting of carbon nanotubes by high-temperature-resistant phenylene and sulfone groups.

[0023] The end-capping agent used in the embodiment of the present invention is characterized by: using a diphenyl sulfone structure constructed by a sulfonation reaction as a primitive, wherein the para position of one phenyl group is replaced by a fluorine or chlorine atom, and the para position of another phenyl group is directly or indirectly connected to an aniline functional group. Among them, the sulfone group is located in the para position of the fluorine (chlorine) atom, which can significantly improve the reaction efficiency of the end-capping agent and can achieve "one-pot" end-capping polymerization. Its synthesis method is: using an amide-containing sulfonyl halide compound and a halogenated benzene as raw materials, preparing an end-capping agent precursor through a sulfonation reaction; converting the amide into an amino group through acid hydrolysis to prepare the end-capping agent. The specific reaction route is as follows: ; Among them, the structural formula of the amide-containing sulfonyl halide compound is: .

[0024] X is F or Cl; the structural formula of R is: ; Correspondingly, The structural formula is: .

[0025] The amino-terminated polyarylether prepared in the embodiment of the present invention is characterized in that the amino-terminated polyarylether is directly prepared by "one-pot" polymerization, and the polymer main chain is connected to the aniline end group through the sulfone group. The "one-pot" polymerization method is: the end-capping agent, the difluoro monomer, the bisphenol monomer and potassium carbonate are added to sulfolane (solvent) at the same time, and the amino-terminated polyarylether is obtained by polymerization after azeotropic dehydration. The specific reaction route is as follows: ; Wherein, the structural formula of bisphenol monomer is any one of the following: ; .

[0026] The structural formula of the difluoro monomer is any of the following: .

[0027] The structural formula of the amino-terminated polyarylether is any one of the following:

[0028] ; Among them, the structural formula of R in these structural formulas is any of the following: .

[0029] The diazonium salt-terminated polyarylether prepared in the embodiment of the present invention is characterized in that the polymer main chain is connected to the phenyl tetrafluoroborate diazonium salt end group through a sulfone group. The implementation method is: the diazonium salt-terminated polyarylether is prepared by reacting nitrosotetrafluoroborate with the diazonium salt of the aniline end group. The specific reaction route is as follows:

[0030] Wherein, the structural formula of the diazonium salt-terminated polyarylether is any one of the following:

[0031] ; Wherein, the structural formula of R1 is any of the following: .

[0032] The polyarylether surface-grafted carbon nanotubes prepared in the embodiment of the present invention are characterized in that the surface of the carbon nanotube paper (bucky paper) or carbon nanotube fiber is directly connected to the polyarylether through the phenyl group and the sulfone group through an efficient electrochemical reduction reaction. The specific method is: connect the carbon nanotube paper (bucky paper) or carbon nanotube fiber to the cathode of the electrolytic cell, immerse it in an electrolyte (containing diazonium salt-capped polyarylether), apply a reduction potential to react, wash and dry to obtain the carbon nanotube grafted with the polyarylether, and its structural formula is as follows: Figure 1 shown. Figure 1 In the invention, the structural formula of the polyarylether is any one of the following:

[0033] .

[0034] The poly(aryletherketone) surface grafted modified carbon nanotubes prepared in the embodiment of the present invention are characterized in that the surface of the carbon nanotubes is directly connected to the crystalline poly(aryletherketone) through the phenyl group and the sulfone group, and the method is: the carbon nanotubes grafted with poly(aryletherketone) are subjected to a hydrolysis reaction in an acidic environment to form crystalline poly(aryletherketone) to obtain crystalline poly(aryletherketone) surface grafted carbon nanotubes, and the structure thereof is as follows: Figure 2 shown. Figure 2 In the invention, the structural formula of the crystalline polyaryletherketone is any one of the following:

[0035]

[0036] ; in addition, Figure 1 and Figure 2 In the formula of R2, any of the following is true: .

[0037] Specifically, in one embodiment of the present invention, a method for preparing carbon nanotubes grafted onto the surface of crystalline poly(aryletherketone) is provided, which comprises the following steps: S1. Under the condition of no more than -5 °C and inert gas protection, fully dissolve the amide-containing sulfonyl halide compound in halogenated benzene (both as solvent and reactant), and add AlCl3 powder (1.2-1.5 times the molar amount of sulfonyl chloride functional group) in batches; then heat to room temperature and stir for 3-5 hours; continue to heat to reflux and stir for 8-10 hours; add deionized water to azeotropic reflux to separate unreacted halogenated benzene; filter, and wash the filter residue with NaOH solution (0.5-1.5 mol / L) and deionized water in turn to obtain a crude product; recrystallize the crude product with ethanol three times, and dry to obtain a capping agent precursor; S2, dissolving the capping agent precursor in a mixture of concentrated hydrochloric acid (0.1-1 mol / L) and ethanol (0.1-1 mol / L) and reflux overnight, followed by extraction with ethyl acetate (80 mL×3). The combined organic phases were dried over anhydrous sodium sulfate, filtered and concentrated to obtain an amino capping agent containing a sulfone group; S3, adding an amino end-capping agent containing a sulfone group (the molar amount of the end-capping agent is 1%-20% of the molar amount of the bisphenol monomer), a difluoro monomer, a bisphenol monomer and potassium carbonate to sulfolane (solvent) at the same time; then adding toluene, heating to azeotropic (130-150°C), maintaining toluene reflux for 3-5 hours, and then draining the toluene; continuing to heat to not less than 210°C for reaction, maintaining for 3-5 hours; then discharging the material into ethanol, crushing it, and washing it with ethanol and water for 3 times each, and drying it to obtain an amino-terminated polyarylether; S4, dissolving the amino-terminated polyarylether in 1,4-dioxane (amino end group equivalent 0.01-0.1 mol / L); dropping the above solution into an acetonitrile solution (0.01-0.1 mol / L) containing nitrite tetrafluoroborate (NOBF4); when the solution becomes a dark brown transparent solution, discharging the solution into ether, rapidly precipitating the diazonium-terminated polyarylether, filtering and washing with ether to obtain the diazonium-terminated polyarylether; S5. Dissolve diazonium salt-capped polyarylether (0.01-0.1 g / mL) and supporting electrolyte (0.5-1.5 mM) in acetonitrile to prepare an electrolyte; connect carbon nanotube paper (bucky paper) or carbon nanotube fiber to the cathode, immerse in the electrolyte, and apply a reduction potential of -0.3 V for 1-5 min. Wash the electrochemically reduced carbon nanotubes with acetonitrile and dry them to obtain carbon nanotubes grafted with polyarylether; S6. Place the carbon nanotubes grafted with polyarylether in acetone (0.01-0.05 g / mL), mechanically stir and ultrasonically disperse for 1-3 hours; under the conditions of mechanical stirring and ultrasonic dispersion, add 1-3 M hydrochloric acid in an equal volume to acetone, raise the temperature to reflux, and maintain for 20-28 hours; then filter, wash with deionized water for several times, and dry to obtain crystalline polyaryletherketone surface grafted carbon nanotubes.

[0038] The following embodiments are some specific implementation cases and application cases of the present invention in practical applications, but are not limited thereto.

[0039] Example 1: This example provides a method for preparing carbon nanotubes grafted onto the surface of crystalline poly(aryletherketone), which specifically comprises the following steps: (1) At -5 °C and under inert gas protection, 4-acetamidobenzenesulfonyl chloride (0.1 mol) was fully dissolved in chlorobenzene (chlorobenzene was used as both solvent and reactant), and AlCl3 powder (0.12 mol) was added in 5 batches; the mixture was heated to room temperature and stirred for 3 hours; the mixture was heated to reflux and stirred for 8 hours; deionized water was added to azeotropically reflux and unreacted chlorobenzene was separated; the mixture was filtered and the residue (crude product) was washed with NaOH solution (1 mol / L) and deionized water in turn; the end-capping agent precursor (N-(4-((4-chlorophenyl)sulfonyl)phenyl)acetamide, corresponding to the above chemical formula: R'=R'-1; X= Cl) was obtained by recrystallization three times with ethanol and drying. The yield was 85%; (2) The end-capping agent precursor obtained in step (2) was dissolved in a mixture of concentrated hydrochloric acid (0.1 mol / L) and ethanol (0.1 mol / L) and refluxed overnight; then extracted with ethyl acetate (80 mL×3), the organic phases were combined and dried over anhydrous sodium sulfate; filtered, the filtrate was collected and the solvent was removed to obtain the end-capping agent (4-chloro-4'-aminodiphenyl sulfone, corresponding to the above chemical formula: R''= R''-1; X= Cl), with a yield of 95%; (3) 0.001 mol of the end-capping agent (4-chloro-4'-aminodiphenyl sulfone) obtained in step (2), 0.1 mol of 4,4'-difluorobenzophenone imine, 0.1 mol of hydroquinone and 0.13 mol of potassium carbonate are added to cyclopentane sulfone (solvent) at the same time; toluene is added, the temperature is raised to azeotropic (130°C), toluene and water are maintained at azeotropic reflux for 4 hours, and toluene is exhausted; the temperature is raised to 210°C and maintained for 4 hours; the material is discharged into ethanol and crushed; the material is washed with ethanol and water three times each, and dried to obtain amino-terminated polyetheretherketoneimine (corresponding to the above chemical formula: NH2-PI-1; R=R1-1); (4) dissolving the amino-terminated polyetheretherketoneimine obtained in step (3) in 1,4-dioxane (amino end group equivalent 0.01 mol / L); adding the above solution dropwise into an acetonitrile solution (0.01 mol / L) containing 1.5 times the amino end group equivalent of tetrafluoroborate nitrite; when the solution becomes a dark brown transparent solution, discharging the solution into ether, the diazonium salt-terminated polyarylether ether is rapidly precipitated, filtered and washed with ether to obtain a diazonium salt-terminated polyetheretherketoneimine (corresponding to the above chemical formula: Dia-PI-1; R1=R1-1); (5) The diazonium salt-terminated polyetheretherketoneimine (0.01 g / mL) obtained in step (4) and a supporting electrolyte (tetrabutylammonium tetrafluoroborate, 1 mM) were dissolved in acetonitrile as an electrolyte; the carbon nanotube paper (buckypaper) was connected to the cathode of the electrolytic cell and immersed in the electrolyte; a reduction potential of -0.3 V was applied and maintained for 3 min to carry out an electrochemical reduction grafting reaction. The cyclic voltammetry curve of the electrochemical reduction grafting reaction is shown in FIG. Figure 4 As shown; the electrochemically reduced carbon nanotubes were washed with acetonitrile and dried to obtain carbon nanotubes grafted with polyetheretherketimine (corresponding to the above chemical structure: PI-1; R2-=R2-1); (6) The carbon nanotubes grafted with polyetheretherketone imine obtained in step (5) were placed in acetone (0.01 g / mL), mechanically stirred and ultrasonically dispersed for 2 hours; under the conditions of mechanical stirring and ultrasonic dispersion, 2 M hydrochloric acid in an equal volume to acetone was added dropwise; under the conditions of mechanical stirring and ultrasonic dispersion, the temperature was raised to reflux and maintained for 24 hours; filtered, washed with deionized water for 3 times, and dried to obtain crystalline polyetheretherketone surface-grafted carbon nanotubes (corresponding to the above chemical structure: P-1; R2-=R2-1). The crystalline polyetheretherketone surface-grafted carbon nanotubes prepared above were characterized by Raman spectroscopy, and the results were as follows: Figure 3 As shown, the results showed that crystalline poly (aryletherketone) was successfully grafted onto the surface of carbon nanotubes.

[0040] Example 2: This example provides a method for preparing carbon nanotubes grafted onto the surface of crystalline poly(aryletherketone), which specifically comprises the following steps: (1) At -5 °C and under inert gas protection, 4'-acetylamino-[1,1'-biphenyl]-4-sulfonyl chloride (0.1 mol) was fully dissolved in fluorobenzene (fluorobenzene was used as both solvent and reactant), and AlCl3 powder (0.15 mol) was added in 5 batches; the mixture was heated to room temperature and stirred for 5 hours; the mixture was heated to reflux and stirred for 10 hours; deionized water was added to azeotropically reflux and unreacted fluorobenzene was separated; the mixture was filtered and the residue (crude product) was washed with NaOH solution (1 mol / L) and deionized water in turn; the end-capping agent precursor (N-(4'-((4-fluorophenyl)sulfonyl)-[1,1'-biphenyl]-4-yl)acetamide)acetamide, corresponding to the above chemical formula: R'= R'-2; X=F) was obtained with a yield of 88%; (2) The end-capping agent precursor obtained in step (1) was dissolved in a mixture of concentrated hydrochloric acid (0.15 mol / L) and ethanol (0.15 mol / L) and refluxed overnight; then extracted with ethyl acetate (80 mL×3), the organic phases were combined and dried over anhydrous sodium sulfate; filtered, the filtrate was collected and the solvent was removed to obtain the end-capping agent (4-fluoro-4'-(4-aminophenyl)diphenyl sulfone, corresponding to the above chemical formula: R''= R''-2; X= F), with a yield of 95%; (3) 0.02 mol of the end-capping agent (4-fluoro-4'-(4-aminophenyl)diphenyl sulfone) obtained in step (2), 0.1 mol of 4,4'-difluorobenzophenone imine, 0.1 mol of 4,4'-dihydroxydiphenyl ether and 0.13 mol of potassium carbonate are added to cyclopentane sulfone (solvent) at the same time; toluene is added, the temperature is raised to azeotropic (130°C), toluene and water are maintained at azeotropic reflux for 4 hours, and toluene is exhausted; the temperature is raised to 210°C and maintained for 4 hours; the material is discharged into ethanol and crushed; the product is washed with ethanol and water three times each, and dried to obtain amino-terminated polyetheretherketoneimine (corresponding to the above chemical formula: NH2-PI-2; R=R-3); (4) dissolving the amino-terminated polyetheretheretherketoneimine obtained in step (3) in 1,4-dioxane (amino end group equivalent 0.1 mol / L); adding the above solution dropwise into an acetonitrile solution (0.1 mol / L) containing 1.5 times the amino end group equivalent of tetrafluoroborate nitrite; when the solution becomes a dark brown transparent solution, discharging the solution into ether, the diazonium salt-terminated polyarylether is rapidly precipitated, filtered and washed with ether to obtain a diazonium salt-terminated polyetheretherketoneimine (corresponding to the above chemical formula: Dia-PI-2; R1=R1-3); (5) Dissolving the diazonium salt-terminated polyetheretherketoneimine (0.01 g / mL) obtained in step (4) and a supporting electrolyte (tetrabutylammonium tetrafluoroborate, 1 mM) in acetonitrile as an electrolyte; connecting the carbon nanotube fiber to the cathode of the electrolytic cell and immersing it in the electrolyte; applying a reduction potential of -0.3 V for 3 min; washing the electrochemically reduced carbon nanotube with acetonitrile and drying it to obtain a carbon nanotube grafted with polyetheretheretherketoneimine (corresponding to the above chemical structure: PI-2; R2=R2-3); (6) The carbon nanotubes grafted with polyetheretheretherketone imine obtained in step (5) are placed in acetone (0.05 g / mL), mechanically stirred and ultrasonically dispersed for 2 hours; under the conditions of mechanical stirring and ultrasonic dispersion, an equal volume of 2 M hydrochloric acid is added dropwise; under the conditions of mechanical stirring and ultrasonic dispersion, the temperature is raised to reflux and maintained for 24 hours; filtered, washed with deionized water for 3 times, and dried to obtain crystalline polyetheretheretherketone surface grafted modified carbon nanotubes (corresponding to the above chemical structure: P-2; R2=R2-3).

[0041] Example 3: This example provides a method for preparing carbon nanotubes grafted onto the surface of crystalline poly(aryletherketone), which specifically comprises the following steps: (1) At -5 °C and under inert gas protection, 4-(4-acetylaminophenoxy)benzenesulfonyl chloride (0.1 mol) was fully dissolved in fluorobenzene (fluorobenzene was used as both solvent and reactant), and AlCl3 powder (0.12 mol) was added in 5 batches; the temperature was raised to room temperature and stirred for 3 hours; the temperature was raised to reflux and stirred for 8 hours; deionized water was added to azeotropic reflux to separate unreacted fluorobenzene; the filter was filtered and the residue (crude product) was washed with NaOH solution (1 mol / L) and deionized water in turn; the end-capping agent precursor (N-(4-(4-((4-fluorophenyl)sulfonyl)phenoxy)phenyl)acetamide, corresponding to the above chemical formula: R'= R'-3; X=F) was obtained with a yield of 85%; (2) The end-capping agent precursor obtained in step (1) was dissolved in a mixture of concentrated hydrochloric acid (0.25 mol / L) and ethanol (0.25 mol / L) and refluxed overnight; then extracted with ethyl acetate (80 mL×3), the organic phases were combined and dried over anhydrous sodium sulfate; filtered, the filtrate was collected and the solvent was removed to obtain the end-capping agent (4-fluoro-4'-(4-aminophenoxy)diphenyl sulfone, corresponding to the above chemical formula: R''= R''-3; X= F), with a yield of 95%; (3) 0.01 mol of the end-capping agent (4-fluoro-4'-(4-aminophenoxy)diphenyl sulfone) obtained in step (2), 0.1 mol of 4,4'-difluorodiketone imine, 0.1 mol of 4,4'-dihydroxydiphenyl ether and 0.13 mol of potassium carbonate are added to cyclopentane sulfone (solvent) at the same time; toluene is added, the temperature is raised to azeotropic (130°C), toluene and water are maintained at azeotropic reflux for 4 hours, and toluene is exhausted; the temperature is raised to 210°C and maintained for 4 hours; the material is discharged into ethanol and crushed; the product is washed with ethanol and water three times each, and dried to obtain amino-terminated polyetheretheretherketoneketimine (corresponding to the above chemical formula: NH2-PI-6; R=R-2); (4) dissolving the amino-terminated poly(ether-ether-ketone-ketone-imine) obtained in step (3) in 1,4-dioxane (amino end group equivalent 0.01 mol / L); adding the above solution dropwise into an acetonitrile solution (0.01 mol / L) containing 1.5 times the amino end group equivalent of tetrafluoroborate nitrite; when the solution becomes a dark brown transparent solution, discharging the solution into ether, the diazonium salt-terminated poly(arylether) is rapidly precipitated, filtered and washed with ether to obtain a diazonium salt-terminated poly(ether-ether-ketone-ketone-imine) (corresponding to the above chemical formula: Dia-PI-6; R1=R1-2); (5) Dissolving the diazonium salt-terminated poly(ether ether ether ketone ketone imine) (0.01 g / mL) obtained in step (4) and a supporting electrolyte (tetrabutylammonium tetrafluoroborate, 1 mM) in acetonitrile as an electrolyte; connecting the carbon nanotube paper (bucky paper) to the cathode of the electrolytic cell and immersing it in the electrolyte; applying a reduction potential of -0.3 V and maintaining it for 3 min; washing the electrochemically reduced carbon nanotubes with acetonitrile and drying them to obtain carbon nanotubes grafted with poly(ether ether ether ketone ketone imine) (corresponding to the above chemical structure: PI-6; R2=R2-2); (6) The carbon nanotubes grafted with polyetheretheretherketoneketoneimine obtained in step (5) are placed in acetone (0.01 g / mL), mechanically stirred and ultrasonically dispersed for 2 hours; under the conditions of mechanical stirring and ultrasonic dispersion, an equal volume of 2 M hydrochloric acid is added dropwise; under the conditions of mechanical stirring and ultrasonic dispersion, the temperature is raised to reflux and maintained for 24 hours; filtered, washed with deionized water for 3 times, and dried to obtain crystalline polyetheretheretherketoneketone surface grafted modified carbon nanotubes (corresponding to the above chemical structure: P-6; R2=R2-2).

[0042] Example 4: This example provides a method for preparing carbon nanotubes grafted onto the surface of crystalline poly(aryletherketone), which specifically comprises the following steps: (1) At -5 °C and under inert gas protection, 4'-acetylamino-[1,1'-biphenyl]-4-sulfonyl chloride (0.1 mol) was fully dissolved in fluorobenzene (fluorobenzene was used as both solvent and reactant), and AlCl3 powder (0.12 mol) was added in 5 batches; the mixture was heated to room temperature and stirred for 3 hours; the mixture was heated to reflux and stirred for 8 hours; deionized water was added to azeotropically reflux and unreacted fluorobenzene was separated; the mixture was filtered and the residue (crude product) was washed with NaOH solution (1 mol / L) and deionized water in turn; the product was recrystallized three times with ethanol and dried to obtain the end-capping agent precursor (N-(4'-((4-fluorophenyl)sulfonyl)-[1,1'-biphenyl]-4-yl)acetamide, corresponding to the above chemical formula: R'= R'-2; X= F), with a yield of 86%; (2) The end-capping agent precursor obtained in step (1) was dissolved in a mixture of concentrated hydrochloric acid (0.35 mol / L) and ethanol (0.35 mol / L) and refluxed overnight; then extracted with ethyl acetate (80 mL×3), the organic phases were combined and dried over anhydrous sodium sulfate; filtered, the filtrate was collected and the solvent was removed to obtain the end-capping agent (4-fluoro-4'-(4-aminophenyl) diphenyl sulfone, corresponding to the above chemical formula: R''= R''-2; X= F), with a yield of 95%; (3) 0.01 mol of the end-capping agent (4-fluoro-4'-(4-aminophenyl)diphenyl sulfone) obtained in step (2), 0.1 mol of 4,4'-difluorobenzophenone imine, 0.1 mol of 4,4'-dihydroxybenzophenone and 0.13 mol of potassium carbonate are added to cyclopentane sulfone (solvent) at the same time; toluene is added, the temperature is raised to azeotropic (130°C), toluene and water are maintained at azeotropic reflux for 4 hours, and toluene is exhausted; the temperature is raised to 210°C and maintained for 4 hours; the material is discharged into ethanol and crushed; the product is washed with ethanol and water three times each, and dried to obtain amino-terminated polyetherketone imine (corresponding to the above chemical formula: NH2-PI-4; R=R-3); (4) dissolving the amino-terminated polyetherketoneimine obtained in step (3) in 1,4-dioxane (amino end group equivalent 0.01 mol / L); adding the above solution dropwise into an acetonitrile solution (0.01 mol / L) containing 1.5 times the amino end group equivalent of tetrafluoroborate nitrite; when the solution becomes a dark brown transparent solution, discharging the solution into ether, the diazonium salt-terminated polyarylether ether is rapidly precipitated, filtered and washed with ether to obtain a diazonium salt-terminated polyetherketoneimine (corresponding to the above chemical formula: Dia-PI-4; R1=R1-3); (5) The diazonium salt-terminated polyetherketimine (0.01 g / mL) obtained in step (4) and a supporting electrolyte (tetrabutylammonium tetrafluoroborate, 1 mM) were dissolved in acetonitrile as an electrolyte; the carbon nanotube paper (buckypaper) was connected to the cathode of the electrolytic cell and immersed in the electrolyte; a reduction potential of -0.3 V was applied and maintained for 5 min; the electrochemically reduced carbon nanotubes were washed with acetonitrile and dried to obtain carbon nanotubes grafted with polyetherketimine (corresponding to the above chemical structure: PI-4; R2=R2-3); (6) The carbon nanotubes grafted with polyetherketone imine obtained in step (5) are placed in acetone (0.01 g / mL), mechanically stirred and ultrasonically dispersed for 2 hours; under the conditions of mechanical stirring and ultrasonic dispersion, an equal volume of 2 M hydrochloric acid is added dropwise; under the conditions of mechanical stirring and ultrasonic dispersion, the temperature is raised to reflux and maintained for 24 hours; filtered, washed with deionized water for 3 times, and dried to obtain crystalline polyetherketone surface grafted modified carbon nanotubes (corresponding to the above chemical structure: P-4; R2=R2-3).

[0043] Example 5: This example provides a method for preparing carbon nanotubes grafted onto the surface of crystalline poly(aryletherketone), which specifically comprises the following steps: (1) At -5 °C and under inert gas protection, 4'-acetylamino-[1,1'-biphenyl]-4-sulfonyl fluoride (0.1 mol) was fully dissolved in fluorobenzene (fluorobenzene was used as both solvent and reactant), and AlCl3 powder (0.12 mol) was added in 5 batches; the temperature was raised to room temperature and stirred for 3 hours; the temperature was raised to reflux and stirred for 8 hours; deionized water was added to azeotropic reflux to separate unreacted fluorobenzene; the filter was filtered and the residue (crude product) was washed with NaOH solution (1 mol / L) and deionized water in turn; the end-capping agent precursor (N-(4'-((4-fluorophenyl)sulfonyl)-[1,1'-biphenyl]-4-yl)acetamide, corresponding to the above chemical formula: R'= R'-2; X= F) was obtained with a yield of 86%; (2) The end-capping agent precursor obtained in step (1) was dissolved in a mixture of concentrated hydrochloric acid (0.48 mol / L) and ethanol (0.48 mol / L) and refluxed overnight; then extracted with ethyl acetate (80 mL×3), the organic phases were combined and dried over anhydrous sodium sulfate; filtered, the filtrate was collected and the solvent was removed to obtain the end-capping agent (4-fluoro-4'-(4-aminophenyl)diphenyl sulfone, corresponding to the above chemical formula: R''= R''-2; X= F), with a yield of 95%; (3) 0.01 mol of the end-capping agent (4-fluoro-4'-(4-aminophenyl)diphenyl sulfone) obtained in step (2), 0.1 mol of 4,4'-difluorodiketone imine, 0.1 mol of hydroquinone and 0.13 mol of potassium carbonate are added to cyclopentane sulfone (solvent) at the same time; toluene is added, the temperature is raised to azeotropic (130°C), toluene and water are maintained at azeotropic reflux for 4 hours, and toluene is exhausted; the temperature is raised to 210°C and maintained for 4 hours; the material is discharged into ethanol and crushed; the material is washed with ethanol and water three times each, and dried to obtain amino-terminated polyetheretherketoneketimine (corresponding to the above chemical formula: NH2-PI-5; R=R-3); (4) dissolving the amino-terminated polyetheretherketoneketimine obtained in step (3) in 1,4-dioxane (amino end group equivalent 0.01 mol / L); adding the above solution dropwise into an acetonitrile solution (0.01 mol / L) containing 1.5 times the amino end group equivalent of tetrafluoroborate nitrite; when the solution becomes a dark brown transparent solution, discharging the solution into ether, the diazonium salt-terminated polyarylether is rapidly precipitated, filtered and washed with ether to obtain a diazonium salt-terminated polyetheretherketoneketimine (corresponding to the above chemical formula: Dia-PI-5; R1=R1-3); (5) Dissolving the diazonium salt-terminated polyetheretherketoneketimine (0.01 g / mL) obtained in step (4) and supporting electrolyte (tetrabutylammonium tetrafluoroborate, 1 mM) in acetonitrile as an electrolyte; connecting the carbon nanotube paper (buckypaper) to the cathode of the electrolytic cell and immersing it in the electrolyte; applying a reduction potential of -0.3 V for 4 min; washing the electrochemically reduced carbon nanotubes with acetonitrile and drying them to obtain carbon nanotubes grafted with polyetheretherketoneketimine (corresponding to the above chemical structure: PI-5; R2-=R2-3); (6) The carbon nanotubes grafted with polyetheretherketoneketimine obtained in step (5) were placed in acetone (0.01 g / mL), mechanically stirred and ultrasonically dispersed for 2 hours; under the conditions of mechanical stirring and ultrasonic dispersion, an equal volume of 2 M hydrochloric acid was added dropwise; under the conditions of mechanical stirring and ultrasonic dispersion, the temperature was raised to reflux and maintained for 24 hours; filtered, washed with deionized water for 3 times, and dried to obtain crystalline polyetheretherketoneketone surface grafted modified carbon nanotubes (corresponding to the above chemical structure: P-5; R2=R2-3).

[0044] Example 6: This example provides a method for preparing carbon nanotubes grafted onto the surface of crystalline poly(aryletherketone), which specifically comprises the following steps: (1) At -5 °C and under inert gas protection, 4'-acetylamino-[1,1'-biphenyl]-4-sulfonyl fluoride (0.1 mol) was fully dissolved in fluorobenzene (fluorobenzene was used as both solvent and reactant), and AlCl3 powder (0.12 mol) was added in 5 batches; the mixture was heated to room temperature and stirred for 3 hours; the mixture was heated to reflux and stirred for 8 hours; deionized water was added to azeotropically reflux and unreacted fluorobenzene was separated; the mixture was filtered and the residue (crude product) was washed with NaOH solution (1 mol / L) and deionized water in turn; the product was recrystallized three times with ethanol and dried to obtain the end-capping agent precursor (N-(4'-((4-fluorophenyl)sulfonyl)-[1,1'-biphenyl]-4-yl)acetamide, corresponding to the above chemical formula: R'= R'-2; X=F), with a yield of 86%; (2) The end-capping agent precursor obtained in step (1) was dissolved in a mixture of concentrated hydrochloric acid (0.56 mol / L) and ethanol (0.56 mol / L) and refluxed overnight; then extracted with ethyl acetate (80 mL×3), the organic phases were combined and dried over anhydrous sodium sulfate; filtered, the filtrate was collected and the solvent was removed to obtain the end-capping agent (4-fluoro-4'-(4-aminophenyl) diphenyl sulfone, corresponding to the above chemical formula: R''= R''-2; X= F), with a yield of 95%; (3) 0.01 mol of the end-capping agent (4-fluoro-4'-(4-aminophenyl)diphenyl sulfone) obtained in step (2), 0.1 mol of 4,4'-difluorobenzophenone imine, 0.1 mol of biphenyl diphenol and 0.13 mol of potassium carbonate are added to cyclopentane sulfone (solvent) at the same time; toluene is added, the temperature is raised to azeotropic (130°C), toluene and water are maintained at azeotropic reflux for 4 hours, and toluene is exhausted; the temperature is raised to 210°C and maintained for 4 hours; the material is discharged into ethanol and crushed; the material is washed with ethanol and water three times each, and dried to obtain amino-terminated biphenyl type polyetheretherketone imine (corresponding to the above chemical formula: NH2-PI-3; R=R-3); (4) dissolving the amino-terminated biphenyl polyetheretherketone imine obtained in step (3) in 1,4-dioxane (amino end group equivalent 0.01 mol / L); adding the above solution dropwise into an acetonitrile solution (0.01 mol / L) containing 1.5 times the amino end group equivalent of tetrafluoroborate nitrite; when the solution becomes a dark brown transparent solution, discharging the solution into ether, the diazonium salt-terminated polyarylether ether is rapidly precipitated, filtered and washed with ether to obtain a diazonium salt-terminated biphenyl polyetheretherketone imine (corresponding to the above chemical formula: Dia-PI-3; R1=R1-3); (5) Dissolving the diazonium salt-terminated biphenyl polyetheretherketone imine (0.01 g / mL) obtained in step (4) and supporting electrolyte (tetrabutylammonium tetrafluoroborate, 1 mM) in acetonitrile as an electrolyte; connecting the carbon nanotube paper (buckypaper) to the cathode of the electrolytic cell and immersing it in the electrolyte; applying a reduction potential of -0.3 V and maintaining it for 3 min; washing the electrochemically reduced carbon nanotubes with acetonitrile and drying them to obtain carbon nanotubes grafted with biphenyl polyetheretherketone imine (corresponding to the above chemical structure: PI-3; R2=R2-3); (6) The carbon nanotubes grafted with biphenyl polyetheretherketone imine obtained in step (5) are placed in acetone (0.01 g / mL), mechanically stirred and ultrasonically dispersed for 2 hours; under the conditions of mechanical stirring and ultrasonic dispersion, an equal volume of 2M hydrochloric acid is added dropwise; under the conditions of mechanical stirring and ultrasonic dispersion, the temperature is raised to reflux and maintained for 24 hours; filtered, washed with deionized water for 3 times, and dried to obtain crystalline biphenyl polyetheretherketone surface grafted modified carbon nanotubes (corresponding to the above chemical structure: P-3; R2=R2-3).

[0045] Example 7: This example provides a method for preparing carbon nanotubes grafted onto the surface of crystalline poly(aryletherketone), which specifically comprises the following steps: (1) At -5 °C and under inert gas protection, 4'-acetylamino-[1,1'-biphenyl]-4-sulfonyl fluoride (0.1 mol) was fully dissolved in fluorobenzene (fluorobenzene was used as both solvent and reactant), and AlCl3 powder (0.12 mol) was added in 5 batches; the mixture was heated to room temperature and stirred for 3 hours; the mixture was heated to reflux and stirred for 8 hours; deionized water was added to azeotropically reflux and unreacted fluorobenzene was separated; the mixture was filtered and the residue (crude product) was washed with NaOH solution (1 mol / L) and deionized water in turn; the product was recrystallized three times with ethanol and dried to obtain the end-capping agent precursor (N-(4'-((4-fluorophenyl)sulfonyl)-[1,1'-biphenyl]-4-yl)acetamide, corresponding to the above chemical formula: R'= R'-2; X=F) with a yield of 86%.

[0046] (2) The end-capping agent precursor obtained in step (1) was dissolved in a mixture of concentrated hydrochloric acid (0.59 mol / L) and ethanol (0.59 mol / L) and refluxed overnight; then extracted with ethyl acetate (80 mL×3), the organic phases were combined and dried over anhydrous sodium sulfate; filtered, the filtrate was collected and the solvent was removed to obtain the end-capping agent (4-fluoro-4'-(4-aminophenyl) diphenyl sulfone, corresponding to the above chemical formula: R''= R''-2; X= F), with a yield of 95%; (3) 0.01 mol of the end-capping agent (4-fluoro-4'-(4-aminophenyl)diphenyl sulfone) obtained in step (2), 0.1 mol of 4,4'-difluorodiketone imine, 0.1 mol of biphenyl diphenol and 0.13 mol of potassium carbonate are added to cyclopentane sulfone (solvent) at the same time; toluene is added, the temperature is raised to azeotropic (130°C), toluene and water are maintained at azeotropic reflux for 4 hours, and toluene is exhausted; the temperature is raised to 210°C and maintained for 4 hours; the material is discharged into ethanol and crushed; the product is washed with ethanol and water three times each, and dried to obtain amino-terminated biphenyl type polyetheretherketoneketimine (corresponding to the above chemical formula: NH2-PI-7; R=R-3); (4) dissolving the amino-terminated biphenyl polyetheretherketoneketimine obtained in step (3) in 1,4-dioxane (amino end group equivalent 0.01 mol / L); adding the above solution dropwise into an acetonitrile solution (0.01 mol / L) containing 1.5 times the amino end group equivalent of tetrafluoroborate nitrite; when the solution becomes a dark brown transparent solution, discharging the solution into ether, the diazonium salt-terminated polyarylether is rapidly precipitated, filtered and washed with ether to obtain a diazonium salt-terminated biphenyl polyetheretherketoneketimine (corresponding to the above chemical formula: Dia-PI-7; R1=R1-3); (5) The diazonium salt-terminated biphenyl polyetheretherketoneketimine (0.01 g / mL) obtained in step (4) and a supporting electrolyte (tetrabutylammonium tetrafluoroborate, 1 mM) were dissolved in acetonitrile as an electrolyte; the carbon nanotube paper (buckypaper) was connected to the cathode of the electrolytic cell and immersed in the electrolyte; a reduction potential of -0.3 V was applied and maintained for 3 min; the electrochemically reduced carbon nanotubes were washed with acetonitrile and dried to obtain carbon nanotubes grafted with biphenyl polyetheretherketoneketimine (corresponding to the above chemical structure: PI-7; R2-=R2-3); (6) The carbon nanotubes grafted with biphenyl polyetheretherketoneketoneimine obtained in step (5) are placed in acetone (0.01 g / mL), mechanically stirred and ultrasonically dispersed for 2 hours; under the conditions of mechanical stirring and ultrasonic dispersion, an equal volume of 2M hydrochloric acid is added dropwise; under the conditions of mechanical stirring and ultrasonic dispersion, the temperature is raised to reflux and maintained for 24 hours; filtered, washed with deionized water for 3 times, and dried to obtain crystalline biphenyl polyetheretherketoneketone surface grafted modified carbon nanotubes (corresponding to the above chemical structure: P-7; R2=R2-3).

[0047] Example 8: This example provides a method for preparing carbon nanotubes grafted onto the surface of crystalline poly(aryletherketone), which specifically comprises the following steps: (1) At -5 °C and under inert gas protection, 4'-acetylamino-[1,1'-biphenyl]-4-sulfonyl fluoride (0.1 mol) was fully dissolved in fluorobenzene (fluorobenzene was used as both solvent and reactant), and AlCl3 powder (0.12 mol) was added in 5 batches; the mixture was heated to room temperature and stirred for 3 hours; the mixture was heated to reflux and stirred for 8 hours; deionized water was added to azeotropically reflux and unreacted fluorobenzene was separated; the mixture was filtered and the residue (crude product) was washed with NaOH solution (1 mol / L) and deionized water in turn; the product was recrystallized three times with ethanol and dried to obtain the end-capping agent precursor (N-(4'-((4-fluorophenyl)sulfonyl)-[1,1'-biphenyl]-4-yl)acetamide, corresponding to the above chemical formula: R'= R'-2; X=F), with a yield of 86%; (2) The end-capping agent precursor obtained in step (1) was dissolved in a mixture of concentrated hydrochloric acid (0.7 mol / L) and ethanol (0.7 mol / L) and refluxed overnight; then extracted with ethyl acetate (80 mL×3), the organic phases were combined and dried over anhydrous sodium sulfate; filtered, the filtrate was collected and the solvent was removed to obtain the end-capping agent (4-fluoro-4'-(4-aminophenyl)diphenyl sulfone, corresponding to the above chemical formula: R''= R''-2; X=F), with a yield of 95%; (3) 0.01 mol of the end-capping agent (4-fluoro-4'-(4-aminophenyl)diphenyl sulfone) obtained in step (2), 0.1 mol of 4,4'-difluorodiketone imine, 0.1 mol of 4,4'-dihydroxybenzophenone and 0.13 mol of potassium carbonate are added to cyclopentane sulfone (solvent) at the same time; toluene is added, the temperature is raised to azeotropic (130°C), toluene and water are maintained at azeotropic reflux for 4 hours, and toluene is exhausted; the temperature is raised to 210°C and maintained for 4 hours; the material is discharged into ethanol and crushed; the product is washed with ethanol and water three times each, and dried to obtain amino-terminated polyetherketoneetherketoneketoneimine (corresponding to the above chemical formula: NH2-PI-8; R=R-3); (4) dissolving the amino-terminated polyetherketoneetherketoneketoneimine obtained in step (3) in 1,4-dioxane (amino end group equivalent 0.01 mol / L); adding the above solution dropwise into an acetonitrile solution (0.01 mol / L) containing 1.5 times the amino end group equivalent of tetrafluoroborate nitrite; when the solution becomes a dark brown transparent solution, discharging the solution into ether, the diazonium salt-terminated polyarylether ether is rapidly precipitated, filtered and washed with ether to obtain a diazonium salt-terminated polyetherketoneetherketoneketoneimine (corresponding to the above chemical formula: Dia-PI-8; R1=R1-3); (5) Dissolving the diazonium salt-capped poly(ether ketone ether ketone ketone imine) (0.01 g / mL) obtained in step (4) and a supporting electrolyte (tetrabutylammonium tetrafluoroborate, 1 mM) in acetonitrile as an electrolyte; connecting the carbon nanotube paper (buckypaper) to the cathode of the electrolytic cell and immersing it in the electrolyte; applying a reduction potential of -0.3 V for 3 min; washing the electrochemically reduced carbon nanotubes with acetonitrile and drying them to obtain carbon nanotubes grafted with poly(ether ketone ether ketone ketone imine) (corresponding to the above chemical structure: PI-8; R2=R2-3); (6) The carbon nanotubes grafted with polyetherketoneetherketoneketoneimine obtained in step (5) are placed in acetone (0.01 g / mL), mechanically stirred and ultrasonically dispersed for 2 hours; under the conditions of mechanical stirring and ultrasonic dispersion, an equal volume of 2 M hydrochloric acid is added dropwise; under the conditions of mechanical stirring and ultrasonic dispersion, the temperature is raised to reflux and maintained for 24 hours; filtered, washed with deionized water for 3 times, and dried to obtain crystalline polyetherketoneetherketoneketone surface grafted modified carbon nanotubes (corresponding to the above chemical structure: P-8; R2-=R2-3).

[0048] Based on the above-mentioned ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above-mentioned description. The technical scope of the present invention is not limited to the contents of the specification.

Claims

1. A method for preparing carbon nanotubes grafted onto the surface of crystalline poly(aryletherketone), characterized in that: The following steps are involved: The amide-containing sulfonyl halide compound and halogenated benzene are sequentially subjected to sulfonation reaction and acid hydrolysis reaction to obtain an amino-terminated agent containing a sulfone group; The amino-terminated agent containing a sulfone group, a difluoro monomer, a bisphenol monomer and potassium carbonate are placed in sulfolane to carry out a polymerization reaction to obtain an amino-terminated polyarylether; The amino-terminated polyarylether is reacted with nitrite tetrafluoroborate to obtain a diazonium salt-terminated polyarylether; The diazonium salt-capped polyarylether is prepared into an electrolyte, the carbon nanotube is connected to a cathode, immersed in the electrolyte containing the diazonium salt-capped polyarylether, and a reduction potential is applied to react to obtain a carbon nanotube grafted with the polyarylether; The carbon nanotubes grafted with polyarylether are subjected to hydrolysis reaction in an acidic environment to obtain crystalline carbon nanotubes grafted with polyaryletherketone surface.

2. The method for preparing crystalline poly(aryletherketone) surface-grafted carbon nanotubes according to claim 1, characterized in that: The halogenated benzene is chlorobenzene or fluorobenzene.

3. The method for preparing crystalline poly(aryletherketone) surface-grafted carbon nanotubes according to claim 1 or 2, characterized in that: The step of sequentially subjecting an amide-containing sulfonyl halide compound and a halogenated benzene to a sulfonation reaction and an acidolysis reaction to obtain an amino end-capping agent containing a sulfone group specifically comprises: Under the condition of no more than -5 ℃ and inert gas protection, the amide-containing sulfonyl halide compound is fully dissolved in the halogenated benzene, and AlCl3 powder is added in batches; then the temperature is raised to room temperature and stirred; the temperature is continued to be raised to reflux; deionized water is added to azeotropic reflux to separate the unreacted halogenated benzene; filtering and washing the filter residue to obtain a crude product; using ethanol to recrystallize the crude product three times, and drying to obtain a capping agent precursor; The capping agent precursor is dissolved in a mixture of concentrated hydrochloric acid and ethanol and refluxed; then extracted with ethyl acetate, the organic phases are combined and dried over anhydrous sodium sulfate; then filtered and concentrated to obtain an amino capping agent containing a sulfone group.

4. The method for preparing crystalline poly(aryletherketone) surface-grafted carbon nanotubes according to claim 1, characterized in that: The difluoro monomer is 4,4'-difluorobenzophenone imine and / or difluorodiketone imine; the bisphenol monomer is at least one of hydroquinone, biphenol, 4,4'-dihydroxybenzophenone and 4,4'-dihydroxydiphenyl ether.

5. The method for preparing crystalline poly(aryletherketone) surface-grafted carbon nanotubes according to claim 1 or 4, characterized in that: The step of placing an amino-terminated agent containing a sulfone group, a difluoro monomer, a bisphenol monomer and potassium carbonate in sulfolane for polymerization reaction to obtain an amino-terminated polyarylether specifically comprises: An amino end-capping agent containing a sulfone group, a difluoro monomer, a bisphenol monomer and potassium carbonate are added to cyclopentane sulfone at the same time; then toluene is added, the temperature is raised to azeotropic, and after toluene is refluxed for a certain period of time, the toluene is exhausted; the temperature is continued to be raised to not less than 210°C for reaction; then the material is discharged into ethanol, crushed, washed, and dried to obtain an amino-terminated polyarylether.

6. The method for preparing crystalline poly(aryletherketone) surface-grafted carbon nanotubes according to claim 1, characterized in that: The step of subjecting the amino-terminated polyarylether to a diazonium salt reaction with nitrosotetrafluoroborate to obtain the diazonium salt-terminated polyarylether specifically comprises: The amino-terminated polyarylether is dissolved in 1,4-dioxane; the above solution is added dropwise into an acetonitrile solution containing nitrite tetrafluoroborate; when the solution becomes a dark brown transparent solution, the material is discharged into ether, and the diazonium-terminated polyarylether is rapidly precipitated, which is filtered and washed with ether to obtain the diazonium-terminated polyarylether.

7. The method for preparing crystalline poly(aryletherketone) surface-grafted carbon nanotubes according to claim 1, characterized in that: The steps of preparing an electrolyte containing diazonium salt-capped polyarylether, connecting carbon nanotubes to a cathode, immersing the carbon nanotubes in the electrolyte containing diazonium salt-capped polyarylether, and applying a reduction potential to react to obtain carbon nanotubes grafted with polyarylether include: The diazonium salt-terminated polyarylether and supporting electrolyte are dissolved in acetonitrile to prepare an electrolyte solution; The carbon nanotubes are connected to a cathode, immersed in an electrolyte, and a reduction potential is applied to react. The electrochemically reduced carbon nanotubes are washed with acetonitrile and dried to obtain carbon nanotubes grafted with polyarylether.

8. The method for preparing carbon nanotubes grafted onto the surface of crystalline poly(aryletherketone) according to claim 7, characterized in that: The supporting electrolyte is tetrabutylammonium tetrafluoroborate.

9. The method for preparing crystalline poly(aryletherketone) surface-grafted carbon nanotubes according to claim 1, characterized in that: The step of subjecting the carbon nanotubes grafted with polyarylether to hydrolysis reaction in an acidic environment to obtain crystalline polyaryletherketone surface-grafted carbon nanotubes specifically comprises: The carbon nanotubes grafted with polyarylether are placed in acetone, mechanically stirred and ultrasonically dispersed; then, hydrochloric acid is added dropwise under the conditions of mechanical stirring and ultrasonic dispersion, and the temperature is raised to reflux; then, filtration and washing are performed, and drying is performed to obtain crystalline polyaryletherketone surface grafted carbon nanotubes.

10. A crystalline poly(aryletherketone) surface-grafted carbon nanotube prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • A method for preparing sulfonated carbon nanotube-grafted hydroxylated polyetheretherketone / polyetheretherketone composite materials

    CN105838086B

  • A modified carbon nanotube and its preparation method, and a polyetheretherketone composite material and its preparation method.

    CN109851731B

  • A high-toughness polyetheretherketone-based antistatic composite material and its preparation method

    CN112940450B

  • Phenolphthalein-based polyaryletherketone-carbon nanotube graft, preparation method thereof, polyether-ether-ketone heat-conducting composite material and preparation method of polyether-ether-ketone heat-conducting composite material

    CN114507356A

  • Preparation method of sulfonated carbon nano tube grafted hydroxylated polyether-ether-ketone / polyether-ether-ketone composite material

    CN105838086A